ONLINE SCAMS AWARENESS AMONG MUSLIM UNIVERSITY STUDENTS IN MALAYSIA - Wan Noor Hazlina Wan Jusoh; Nurin Munirah Shahrul Nizar (Journal of Islamic, Social, Economics and Development, 2022)
Online scams are not something new in Malaysia. Moreover, during the Movement Control Order (MCO), people are not allowed to go out to buy things, thus the demand for online shopping is high among consumers. Other than that, many victim’s loss a lot of money from online scams cases that lead to more than a million Ringgit Malaysia. Thus, this study was constructed to answer a problem related to online scams. The research objective is to investigate the Malaysian Muslim university student’s awareness on online scams. In this study, the researcher used Google Form to collect data from the respondents. Findings from this study were, the Muslim university students were aware on online scams and they applied the role of religiosity while using online applications and websites.